ANALISIS PENDAPATAN USAHATANI BUNGA PEPAYA DI DESA LIKUPANG KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA Farmer Income (Analysis of Papaya Flower in Likupang Village, District of East Likupang North Minahasa Regency) - Pricilia Jenifer Feren Tumigolung; Agnes Estephina Loho; Theodora M. Katiandagho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze the income and feasibility of papaya     flower farming in Likupang Village District of East Likupang North Minahasa Regency. The method that has been used in this study was case study method. The data used  in this study was primary and secondary data. Primary data was done by direct interview to farmers by using  questionnaire, while for secondary data was done from those who relate, village head office, district office, and also the internet.  Data analysis in this study by used  farming income and R/C .The result of this research showed that the land area of respondent farmer is 0,8 Ha. The total revenue was Rp8.510.000/month, the total cost was Rp2.253.500/month. The Farmer’s income was Rp6.256.500/month. The of papaya     flower farming  due to  rate of R/C was 3,78.